An interactive video to demonstrate the main features of the pendulum - Cardoso, Alberto (2014)
This extended abstract describes an interactive video produced to demonstrate the main features of the pendulum. This module is based on hypermedia contents and can be delivered in a web course about Physics for distance learning either in the e-learning or b-learning format. In this demonstration, the interactive video includes videos of real life scenarios where the pendulum motion is present. After the contextualization, user can choose his own strategy to learn about the pendulum, since the video is prepared for interaction. This feature is particularly important for secondary education and also for lifelong learning courses, for whom access to real laboratories can be more difficult and limited.